2014
DOI: 10.1136/bmjopen-2014-006447
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical features of ovarian pregnancy: a case–control study

Abstract: ObjectiveTo identify risk factors for ovarian pregnancy (OP) and compare clinical features between OP and tubal pregnancy (TP) patients.DesignCase–control study.SettingUniversity hospital.ParticipantsA case–control study was conducted from January 2005 to May 2014. Women diagnosed with OP were recruited as the case group (n=71), 145 women with TP and 146 with intrauterine pregnancy (IUP) were matched as controls at a ratio of 1:2:2. Women who refused interviews or provided incomplete information were excluded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Risk factors for ovarian pregnancy include pelvic inflammatory disease, previous gynecologic surgery, endometriosis, intrauterine device usage, and in vitro fertilization (IVF). 11,12 Ovarian implantation may occur secondary to reflux of the fertilized egg from the fallopian tube or following intrafollicular fertilization. The mechanism of reverse migration, which explains the occurrence of ovarian pregnancies following IVF, may not be solely elucidative, for a literature search yielded several reports of ovarian pregnancies following IVF but only seven following IUI (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for ovarian pregnancy include pelvic inflammatory disease, previous gynecologic surgery, endometriosis, intrauterine device usage, and in vitro fertilization (IVF). 11,12 Ovarian implantation may occur secondary to reflux of the fertilized egg from the fallopian tube or following intrafollicular fertilization. The mechanism of reverse migration, which explains the occurrence of ovarian pregnancies following IVF, may not be solely elucidative, for a literature search yielded several reports of ovarian pregnancies following IVF but only seven following IUI (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers consider that the risk factors for ovarian pregnancy are different from the traditional risk factors for tubular pregnancy. In studies it has been found that in vitro fertilization-embryo transfer (IVF-ET) and use of current intrauterine device (IUD) are the risk factors of ovarian pregnancy (12). The incidence of ovarian pregnancy following IVF-ET has been much higher than following natural conception, respectively 6% and 3% of all ectopic pregnancies (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although the embryos are transferred into the endometrial cavity following IVF, retrograde migration of the embryo toward the tube may cause an ectopic implantation in the tube, ovary, or peritoneum. Therefore, IVF‐embryo transfer (ET) has been reported as a risk factor for ectopic pregnancy, including ovarian pregnancy . The cleaving embryo transferred into the endometrial cavity seems to migrate toward the tube during its cleavage to a blastocyst .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IVFembryo transfer (ET) has been reported as a risk factor for ectopic pregnancy, including ovarian pregnancy. 4,5 The cleaving embryo transferred into the endometrial cavity seems to migrate toward the tube during its cleavage to a blastocyst. 6 In contrast, a fully matured blastocyst seems to implant quickly in the endometrium once it is transferred into the endometrial cavity.…”
Section: Discussionmentioning
confidence: 99%